Development of a structural model with dynamic thermal conductivity for composite phase change materials: Numerical and experimental investigations - Feng Hou; Leilei Li; Xiaoning Cai; Hairuo Wang; Nina Gong; Yazhi Zhu; Hui Wang (Case Studies in Thermal Engineering)
To address the thermal regulation optimization of composite phase change materials (CPCMs) in building envelopes, this study proposes a three-dimensional heat transfer model incorporating dynamic effective thermal conductivity. The model explicitly considers the random distribution of spherical phase change macrocapsules (SPCMs) with metal shell thickness of 0.445 mm within a cementitious matrix. Innovatively, the enhanced heat transfer effect from natural convection in liquid PCM is dynamically coupled into the effective thermal conductivity, enabling real-time coupling between mesoscale structural changes and macroscopic thermal response. Experimental validations demonstrate that the model exhibits high prediction accuracy for temperature fluctuations on the phase-change plateau and energy storage efficiency. Parametric analyses reveal that increasing the SPCMs volume fraction from 5.07 % to 24.86 % extends the duration of the phase-change plateau by 147.4 % and enhances the latent heat storage density by 400 %. Furthermore, elevating PCM latent heat from 140 kJ/kg to 260 kJ/kg results in a total energy storage capacity increase of 31.1 %. However, increasing the phase-change temperature from 27 °C to 33 °C significantly decreases the storage efficiency by 81.3 %, highlighting a critical trade-off between material thermodynamic properties and environmental compatibility. This research provides essential theoretical insights for performance optimization of CPCMs in green building systems.